Developmental Changes in Peripherin-eGFP Expression in Spiral Ganglion Neurons - Elliott, Karen L.; Kersigo, Jennifer; Lee, Jeong Han; Jahan, Israt; Pavlinkova, Gabriela; Fritzsch, Bernd; Yamoah, Ebenezer N. (Frontiers in Cellular Neuroscience, 2021)
The two types of spiral ganglion neurons (SGNs), types I and II, innervate inner hair cells and outer hair cells, respectively, within the mammalian cochlea and send another process back to cochlear nuclei in the hindbrain. Studying these two neuronal types has been made easier with the identification of unique molecular markers. One of these markers, peripherin, was shown using antibodies to be present in all SGNs initially but becomes specific to type II SGNs during maturation. We used mice with fluorescently labeled peripherin (Prph-eGFP) to examine peripherin expression in SGNs during development and in aged mice. Using these mice, we confirm the initial expression of Prph-eGFP in both types I and II neurons and eventual restriction to only type II perikarya shortly after birth. However, while Prph-eGFP is uniquely expressed within type II cell bodies by P8, both types I and II peripheral and central processes continue to express Prph-eGFP for some time before becoming downregulated. Only at P30 was there selective type II Prph-eGFP expression in central but not peripheral processes. By 9 months, only the type II cell bodies and more distal central processes retain Prph-eGFP expression. Our results show that Prph-eGFP is a reliable marker for type II SGN cell bodies beyond P8; however, it is not generally a suitable marker for type II processes, except for central processes beyond P30. How the changes in Prph-eGFP expression relate to subsequent protein expression remains to be explored.